Influence of Biopores Infiltration Holes on the Level Erosion in Oil Palm Plantations Area - Devianti; Irwansyah; Yunus, Yuswar; Arianti, Nunik Destria; Thamren, Dewi Sartika; Sitorus, Agustami (My University, 2022)
The extension of oil palm plantations in Indonesia has encroached on land with a slope of more than 15%, which impacts the possibility of erosion and landslides. However, conservation efforts to reduce erosion are yet to be fully established. Therefore, the present work studies the effect of biopores infiltration holes on erosion at oil palm plantations area with land slopes greater than 15%. Besides, surface runoff with erosion is modeled to find the relationship. The method used in this study is to combine mechanical conservation methods in the form of biopores infiltration holes in an area that already has cover crops, such as Mucuna Bracteata. Two experimental plots were designed, namely (i) plots without biopores infiltration holes and (ii) plots with biopores infiltration holes. The results showed that soil erodibility in the oil palm plantations area was of a high of 0.65. Applying biopores infiltration holes in the field reduced surface runoff and erosion rates by 31.81% and 29.66%, respectively. The relationship of surface runoff with erosion rates on the land shows a very close case where the coefficient of determination in each plot is 0.96 and 0.92.
Keywords: Aceh; appropriate technology; conservation; erosion rates; sloping land; surface runoff